Analisis Kualitas dan Kepuasan Pengguna Website PT Olagafood Berdasarkan Metode WebQual 4.0 - Meivany (Fakultas Komputer - Universitas Universal, 2022)
The internet has become a mainstay for business people and companies today. The increase in internet users in the world makes it easier for companies to market and develop their business fields for consumers to be able to choose goods or services as efficiently as possible. Likewise with PT Olagafood, to make it easier to access information quickly and accurately, a web-based facility was built, namely olagafood.co.id. This website accommodates various information related to products that are being and have been developed by PT. Olagafood. Currently the olagafood.co.id website has not been successfully utilized by the community to the maximum seen from the small number of website visitors, this may be related to user satisfaction in utilizing the information contained in it. From the problems above, an analysis of the extent of user satisfaction in using the website uses the WebQual 4.0 method. It is hoped that user satisfaction has been met, the number of visitors can be increased and the website can be said to have been utilized properly.